Research on the enhancement and key technologies of 5G network for satellite-terrestrial integration - ZHANG Jianyin; NI Lingfei; WANG Hanbai; GU Shangming; LIU Yu; LIU Jinglei (Dianxin kexue)
Satellites have the advantages of complementing terrestrial 5G network in terms of coverage, reliability and flexibility, especially the integration of low earth orbit (LEO) satellite and the terrestrial 5G network has been one of the hot topics in the industry. The enhanced 5G network architecture and related key technologies for satellite-terrestrial integration were primarily introduced. Firstly, the development trends in the field of satellite-terrestrial integration were analyzed and key application scenarios were listed. Secondly, two enhanced 5G network architectures were introduced, which involved transparent relay satellites and renewable satellites. Finally, the related key technologies were analyzed for the business requirements of satellite-terrestrial integrated communication and the brief summary was given, which provided useful reference for the application of 5G satellite-terrestrial integration.